Canadian Public Health Laboratory Network laboratory Guidelines for the Use of Point-of-Care Tests for the Diagnosis of Syphilis in Canada - Ameeta E Singh; Max A Chernesky; Muhammad Morshed; Tom Wong (Canadian Journal of Infectious Diseases and Medical Microbiology)
Syphilis point-of-care tests (POCT) are widely available in developing countries enabling early diagnosis, treatment and support. The majority of commercially available tests use treponemal antigens and the presence of antibodies does not distinguish between current and past infection, which may lead to unnecessary antibiotic use and stigmatization of having a current STI. In hard-to-reach populations, the benefits may outweigh the risks. Available studies show reasonable performance of POCT with median sensitivity of 86%, specificity of 99% and positive predictive values >80% when prevalence was >0.3%. Although no syphilis POCT are approved in Canada at this time, a single study in an outreach setting in Alberta showed limited benefit due to a high prevalence of previous infection but more studies are needed. Newer dual tests employing treponemal and nontreponemal antigens look promising.